Route profiling - putting context to work. - CAHILL, VINNY (ACM Press, 2004)
Intelligent Transportation Systems are characterised by a requirement for detailed information on extensive transport networks. This information is typically gathered from sensors deployed throughout the network and is used for management and maintenance operations. In this paper we present the design and prototype implementation of a context-aware route profiling application intended for use by road management authorities in the Republic of Ireland. Our design allows data from a variety of sources to be combined to generate detailed information on traffic flow and journey times along the national road network. This information can be tagged with relevant context data reflecting the conditions under which sensor data was collected. The set of relevant contextual information includes details on temporal, spatial, weather and road usage pattern contexts. The prototype implementation relies on GPS data from a fleet of probe vehicles. An evaluation of this prototype is presented along with a discussion on the benefits of using context-aware computing techniques in a real world scenario.
Proceedings of the 19th ACM Symposium on Applied Computing (Ubiquitous Computing Applications track),
19th ACM Symposium on Applied Computing (Ubiquitous Computing Applications track)
PUBLISHED
.
Keywords: Ubiquitous Computing, ITS, Context-Aware